Properties of Interrogative and Relative Pronouns and the Differences between Them - Gabrovšek, Dejan (Jezikoslovni zapiski, 2025)
This article presents the main differences between interrogative and relative pronouns and describes the syntactic positions they appear in. The main differences between interrogative and relative pronouns lie in their meaning, syntactic positions, the possibility of coordinate conjunction, and the possibility of ellipsis. Kaj and kar are the only pronouns.